Investigation of Philometra spp. Nematodes Infecting the Gonads of Pagrus pagrus Fish in Sirte, Libya - Ahmed Almashai (AlQalam Journal of Medical and Applied Sciences, 2025)
The Libyan city of Sirte is distinguished by an important geographical location overlooking the coast of the Mediterranean Sea. This coast is full of many fish species, which negatively affect the quality of the sea and are considered an important indicator of pollution in the region. Among the important fish species in this region and in great demand among the population is the Pagrus pagrus fish. Parasite worms infect many species of fish and cause them many damages that negatively affect the growth of these fish and consequently their weight and the amount of meat in them, as well as affecting their reproduction, especially when these parasitic worms infect the gonads of these fish. This study was aimed to verify and describe the presence of Philometra sp in Pagrus pagrus fish in the marine waters of the city of Sirte and isolate these worms. This study was conducted from May 2022 to October 2023. About 110 samples of Pagrus pagrus fish were collected from the seashore of the city of Sirte, Libya. These samples were transferred to the Zoology Laboratory, Science Faculty, Sirte University. Various measurements were taken for each sample. After that, each sample was dissected using special dissection tools. After the dissection was completed and the sample was opened, the internal viscera as well as the gonads of each sample were taken out, and the gonads were placed in a Petri dish containing a saline solution with a concentration of 5%. The gonads were dissected and examined under appropriate lighting, and nematode parasite worms (Philometra sp) were extracted. The results indicated that 27 fish out of a total of 110 examined were infected, with female fish being more infected than males, with an infection rate of 22 out of a total of 40, while 5 infected males out of a total of 70 fish examined.